The Basics of Educational Podcasting: Enhancing the Student Learning Experience - Jamie S. Foster; Stephanie A. Havemann (EDIS, 2008)
MB004, a 6-page illustrated fact sheet by Jamie S. Foster and Stephanie A. Havemann, presents a brief tutorial for educators interested in generating and publishing their own podcasts and discusses the role of podcasting in the classroom. Includes references. Published by the UF Department of Microbiology and Cell Sciences, July 2008.